PELATIHAN VIDEO EDITING BAGI GURU-GURU SEKOLAH MINGGU JEMAAT GKI MARTIN LUTHER SENTANI - Tiku Tandiangnga; Yokelin Tokoro; Tasya Irensia Alfin (LPPM Uncen, 2023)
Gereja Kristen Injili (GKI) Martin Luther Sentani is one of the churches located in Sentani District, Jayapura. Based on interviews with several Sunday school teachers, information was obtained that Sunday school worship is carried out online. However, in making Sunday school worship videos, there are several problems, such as the lack of professional IT staff, some Sunday school teachers can only edit videos via handphones, and the knowledge of Sunday school teachers about software for editing videos on PC or laptops is very low. Taking into account these problems, the Sunday school teachers in this case Badan Pengurus PAR GKI Martin Luther Sentani and the service team deem it necessary to hold activities that involve Sunday school teachers in editing online Sunday school worship videos so that there is a lack of IT personnel. in video editing can be fulfilled even though not professionally. The purpose of this activity is to inform or introduce filmora software for video editing and to hone the skills of Sunday school teachers in video editing. In the implementation of this service activity, several methods were used, namely: the lecture method, the question and answer method, and demonstration. Overall this activity went well. Participants enthusiastically participated in this service activity starting from introductions, delivery and explanation of material, and practice in editing and making videos. With this activity, you can increase or increase knowledge and hone the skills of trainees in editing videos using Filmora X software.Keywords: Sunday school teachers; multimedia; video; video editing; filmora